The Intellectual Dimension of Jesuit Ministries - Peter-Hans Kolvenbach (Jesuit University Ignatianum in Krakow, 2017)
It is a source of great joy for me to meet with our collaborators in this magnificent Aula Magna of the Ignatianum and to share some insights with you on the intellectual apostolate. You have a right to know how we Jesuits perceive the nature and mission of our educational institutions. Even university and cultural circles beyond our own Jesuit works seek to know the spirit with which the Society of Jesus enters the world of science, research, academic instruction, and cultural activity in general. My reflections today are also meant to assist and encourage the process the Polish Jesuits have undertaken of defining their rapidly growing presence in the sector of education after the fall of communism. All this is taking place in conjunction with the worldwide assessment by the Society of our commitment to university education and the role we intend to play in it.